2018
DOI: 10.1097/ccm.0000000000003263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Very Early Physical Therapy During Septic Shock on Skeletal Muscle: A Randomized Controlled Trial

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 42 publications
2
75
0
9
Order By: Relevance
“…These findings are in line with recently published data by Hickmann et al presenting a pilot trial where very early mobilization including bed cycling of septic patients led to preservation of myocyte cross-sectional area. 24 Interestingly, our finding cannot be attributed to an intervention-associated suppression of muscle protein degradation, because MuRF-1 and Atrogin-1 gene expression and protein content were increased in the control and intervention group. It rather can be attributed to an increase in myosin heavy chain gene expression indicating that the muscle protein synthesis pathway was activated.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…These findings are in line with recently published data by Hickmann et al presenting a pilot trial where very early mobilization including bed cycling of septic patients led to preservation of myocyte cross-sectional area. 24 Interestingly, our finding cannot be attributed to an intervention-associated suppression of muscle protein degradation, because MuRF-1 and Atrogin-1 gene expression and protein content were increased in the control and intervention group. It rather can be attributed to an increase in myosin heavy chain gene expression indicating that the muscle protein synthesis pathway was activated.…”
Section: Discussionmentioning
confidence: 57%
“…In this special patient cohort, there is no evidence regarding the molecular effect of early mobilization except a pilot trial by Hickmann et al . lacking clinical data . Our randomized trial is unique because it is the first that enables the interpretation of a broad molecular characterization in the light of clinical outcome data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early mobilization, or exercise after recovery, is a well-known prevention method to prevent sepsis complications (6) and the American College of Critical Care Medicine (ACCM) emphasizes that early mobilization plays a key role for preventing delirium (7). Early mobilization is de ned as applied physical activity within the rst 2 to 5 days of critical illness or injury (8), and a recent randomized, clinical study revealed that early mobilization during septic shock prevents muscle atrophy (9). Implicated pathways for muscle atrophy during sepsis include the mammalian target of rapamycin (MTor)(10), interleukin-6 (IL-6)(11), and tumor necrosis factor-alpha (TNF-α) (12).…”
Section: Introductionmentioning
confidence: 99%